2014
DOI: 10.1093/nar/gku713
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of the interferon response by an interferon-induced long non-coding RNA

Abstract: Long non-coding RNAs (lncRNAs) play critical roles in diverse cellular processes; however, their involvement in many critical aspects of the immune response including the interferon (IFN) response remains poorly understood. To address this gap, we compared the global gene expression pattern of primary human hepatocytes before and at three time points after treatment with IFN-α. Among ∼200 IFN-induced lncRNAs, one transcript showed ∼100-fold induction. This RNA, which we named lncRNA-CMPK2, was a spliced, polya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
269
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(286 citation statements)
references
References 71 publications
11
269
1
1
Order By: Relevance
“…Other antiviral-related lncRNAs such as NRAV and lncRNA-CMPK2 are also negative regulators of antiviral gene expression, including ISGs (20,21). Moreover, previous studies reported that BISPR positively regulates the expression of BST2, which is a protein-coding ISG (22,23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other antiviral-related lncRNAs such as NRAV and lncRNA-CMPK2 are also negative regulators of antiviral gene expression, including ISGs (20,21). Moreover, previous studies reported that BISPR positively regulates the expression of BST2, which is a protein-coding ISG (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…A number of lncRNAs are induced by viral infection or IFN-β (18,19). lncRNA-CMPK2, which is stimulated by IFN-α through the JAK-STAT pathway, suppresses the expression of ISGs such as IFIT3, ISG15, and IFITM1 (20). Influenza A virus-induced lncRNA (NRAV) inhibits the host response to viral infection by suppressing ISG expression (21).…”
mentioning
confidence: 99%
“…A commonly used JAK inhibitor is the small molecule ruxolitinib [111]. Ruxolitinib potently inhibits the phosphorylation of JAK1 and can therefore interrupt IFN-JAK-STAT signaling in mRNAstimulated cells.…”
Section: Inhibition Of the Ifn-induced Effectsmentioning
confidence: 99%
“…Among all types of ncRNAs, long non-coding RNAs (lncRNAs), a regulatory ncRNAs, play critical roles in almost every aspect of cellular processes [8]. Quan Zhang et al found NEAT1 to be one of several lncRNAs whose expression is changed by HIV-1 infection, and the knockdown of NEAT1 enhanced HIV-1 production through increased nucleus-to-cytoplasm export of Rev-dependent instability element (INS)-containing HIV-1 mRNAs [9].…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Hiroto Kambara et al reported that IFN-induced lncRNA-CAPK2 has an inhibitory effort on transcription of IFNstimulated antiviral genes, which suggest that CMPK2 acts as a negative regulator of IFN response [8]. Despite these discoveries, the role of lncRNAs in key aspects of the immune response, including the nearly ubiquitous and functionally crucial interferon (IFN) response remains to further investigation.…”
Section: Introductionmentioning
confidence: 99%